2005
DOI: 10.1158/0008-5472.can-04-3605
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Metalloproteinase Inducer Stimulates Tumor Angiogenesis by Elevating Vascular Endothelial Cell Growth Factor and Matrix Metalloproteinases

Abstract: Matrix metalloproteinases (MMPs) are endopeptidases that play pivotal roles in promoting tumor disease progression, including tumor angiogenesis. In many solid tumors, MMP expression could be attributed to tumor stromal cells and is partially regulated by tumor-stroma interactions via tumor cell-associated extracellular matrix metalloproteinase inducer (EMMPRIN). The role of EMMPRIN during tumor angiogenesis and growth was explored by modulating EMMPRIN expression and activity using recombinant DNA engineering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
268
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(296 citation statements)
references
References 25 publications
21
268
1
6
Order By: Relevance
“…In previous in vitro studies, proteolytic cleavage leading to the shedding of EMMPRIN was suggested to occur at the region of the molecule proximal to the plasma membrane (25,29), although the actual fragments released into the CM had not been characterized clearly. The 22-kDa fragment we detected had not been detected in previous studies, perhaps because the 22-kDa fragment cannot be detected by antibodies that recognize the membrane-proximal region of EMMPRIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous in vitro studies, proteolytic cleavage leading to the shedding of EMMPRIN was suggested to occur at the region of the molecule proximal to the plasma membrane (25,29), although the actual fragments released into the CM had not been characterized clearly. The 22-kDa fragment we detected had not been detected in previous studies, perhaps because the 22-kDa fragment cannot be detected by antibodies that recognize the membrane-proximal region of EMMPRIN.…”
Section: Discussionmentioning
confidence: 99%
“…The other pathway is proteolytic shedding. In addition to inducing MMPs, EMMPRIN is likely to be cleaved and shed by MMPs or other metalloproteinases, because the shedding of EMMPRIN is inhibited by zinc chelators (25,29). Supporting this, MMP-1 and MMP-2 can cleave EMMPRIN at the membrane-proximal region, at least in vitro (29).…”
mentioning
confidence: 99%
“…[115][116][117][118] The fibroblast response is hardwired in the genome as part of the cancer's resemblance to a chronic wound, aiming at support of epithelial cell survival and expansion. [119][120][121][122][123][124][125][126][127][128] In addition to parsimony, this hypothesis offers clear predictions to scientifically test against corresponding null hypotheses; (1) That co-culture of cancer cells with normal fibroblasts will induce expression of CAF-specific genes in the fibroblasts, [63][64][65][66][67][68][69][70][71] [63][64][65][66][67][68][69][70][71] Many of the genes shown to be activated in these co-cultures are known markers of CAFs in vivo, such as MMP1, MMP3, collagens, TNC, etc. Evidence that this reciprocal interaction promotes cancer includes the anti-cancer effect of Imatinib, on carcinoma animal models.…”
Section: The Reciprocal Interactions Model Of Cafsmentioning
confidence: 99%
“…Accordingly, MDA-MB-436 human breast cancer cells recombinantly engineered to overexpress EMMPRIN adopt both accelerated growth and increased invasiveness in vivo. 4 More recently, an involvement of tumor-derived EMMPRIN in tumor angiogenesis through stimulation of MMPs and VEGF production was demonstrated by Tang et al, 5 suggesting that EMMPRIN could represent a key player in tumor cell invasion and metastasis.…”
mentioning
confidence: 99%